Bank efficiency and interest rate pass-through: Evidence from Czech loan products - Tomáš Havránek; Zuzana Havránková; Jitka Lešanovská (Charles University in Prague, Institute of Economic Studies (IES), 2015)
An important component of monetary policy transmission is the pass-through from financial market interest rates, directly influenced or targeted by central banks, to the rates that banks charge firms and households. Yet the available evidence on the strength and speed of the pass-through is mixed and varies across countries, time periods, and even individual banks. We examine the pass-through mechanism using a unique data set of Czech loan and deposit products and focus on bank-level determinants of pricing policies, especially cost efficiency, which we estimate employing both stochastic frontier and data envelopment analysis. Our main results are threefold: First, the long-term pass-through was close to complete for most products before the financial crisis, but has weakened considerably afterward. Second, banks that provide high rates for deposits usually charge high loan markups. Third, cost-efficient banks tend to delay responses to changes in the market rate, smoothing loan rates for their clients.
Keywords: E43; E58; G21; 330; monetary transmission; cost efficiency; bank pricing policies; stochastic frontier analysis; data envelopment analysis